Meditasi dari Depan Layar: Etnografi Digital pada Komunitas Meditasi Online - Wirawan, Wirawan (Jurnal Media dan Komunikasi Indonesia, 2025)
This study examines how traditional forms of religious authority are undergoing change alongside the increasing use of digital media in religious practices. Using a digital ethnographic method, the research was conducted on an online meditation community guided by Samanera Abhisarano from December 2021 to July 2022. Participant observation was carried out online through a WhatsApp group and Zoom meditation sessions, as well as on-site at Vihara Dhammadipa Arama, where Samanera Abhisarano leads meditation remotely. In-depth interviews were conducted with the spiritual guide and five community members. Referring to Campbell’s (2007) framework of religious authority, the study reveals that traditional forms of authority tend to be preserved, although in practice they undergo several adaptations. These findings support previous studies suggesting that, in certain contexts, the adoption of digital media does not weaken traditional religious authority, but rather reinforces it, particularly when it is managed by religious leaders. This research contributes to the ongoing discourse on media and religion from the perspective of a Buddhist community in Indonesia, where the majority of the population is Muslim.